Review of Kyotorphin Research: A Mysterious Opioid Analgesic Dipeptide and Its Molecular, Physiological, and Pharmacological Characteristics - Ueda, Hiroshi (Frontiers in Medical Technology, 2021)
Tyrosine-arginine (kyotorphin), an opioid analgesic dipeptide, was discovered more than 40 years ago in 1979. The evidence accumulated during this period has established the physiological significance of kyotorphin as a neuromodulating peptide, and pharmacological applications. Some of the following important findings have been discussed in this review: 1) kyotorphin is unevenly distributed in the brain; it is found in high concentrations in the pain pathway, which involves the regions associated with morphine analgesia; 2) kyotorphin is subcellularly localized in the synaptosome fraction or nerve-ending particles; 3) a specific synthetase generates kyotorphin from tyrosine and arginine; 4) kyotorphin may be also processed from calpastatin by a novel calcium-activated neutral protease or calpain; 5) kyotorphin preloaded into the synaptosome is released by high K+ depolarization in a Ca2+-dependent manner; 6) kyotorphin has a specific G protein coupled receptor, which mediates the activation of phospholipase C (PLC) and inhibition of adenylyl cyclase through Gi; 7) leucine-arginine works as a specific kyotorphin receptor antagonist; 8) membrane-bound aminopeptidase or excretion through a peptide transporter, PEPT2, may contribute to the inactivation of kyotorphin; and 9) kyotorphin causes increased Met-enkephalin release from brain and spinal slices. It is also known that the opening of plasma membrane Ca2+ channels through a conformational coupling of the InsP3 receptor with the transient receptor potential C1, which is downstream of the kyotorphin receptor-mediated activation of Gi and PLC, could be a potential underlying mechanism of Met-enkephalin release. Considering these findings, translational research is an exciting domain that can be explored in the future. As kyotorphin is a small molecule, we could design function-added kyotorphin derivatives. These studies would include not only the brain-permeable kyotorphin derivatives but also hybrid kyotorphin derivatives conjugated with small compounds that have additional pharmacological actions. Further, since there are reports of kyotorphin being involved in either the etiology or treatment of Alzheimer’s disease, epilepsy, inflammation, and chronic pain, studies on the beneficial effects of kyotorphin derivatives should also be expected in the future.